2021
DOI: 10.1016/j.celrep.2021.110181
|View full text |Cite
|
Sign up to set email alerts
|

Substratum stiffness regulates Erk signaling dynamics through receptor-level control

Abstract: Highlights d Soft substrata decrease the amplitude and frequency of Erk dynamics d The intracellular EGFR/Erk pathway remains signaling competent on soft substrata d Soft substrata decrease the efficiency of EGFR activation and EGF membrane binding d Overexpressing EGFR is sufficient to increase Erk signaling on soft substrata Authors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 61 publications
2
51
0
Order By: Relevance
“…Earlier studies have shown that ERK/MAPK signalling plays a key role in regulation of mesenchymal stem cell differentiation (50). It is now known that stiff substrate promotes osteogenesis by activating ERK signalling pathway while soft substrate downregulates activated ERK Signalling pathway and promotes adipogenesis (51). Hence, we Investigated if VA overwrites the effect of substrate stiffness on osteo/adipo lineage specification via regulating ERK.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies have shown that ERK/MAPK signalling plays a key role in regulation of mesenchymal stem cell differentiation (50). It is now known that stiff substrate promotes osteogenesis by activating ERK signalling pathway while soft substrate downregulates activated ERK Signalling pathway and promotes adipogenesis (51). Hence, we Investigated if VA overwrites the effect of substrate stiffness on osteo/adipo lineage specification via regulating ERK.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, despite a difference in stiffness, both 2D and 3D culture environments led to significant sarcomere disassembly in caBraf-expressing CMs. While the relatively soft ECTs could attenuate endogenous ERK signaling at the level of membrane receptors 74 , the constitutively active BRAF-driven intracellular signaling transmission and ERK activation were likely stiffness- and environment-independent. Sarcomere disassembly was also observed in mouse hearts in vivo upon transient activation of caERBB2 and ERK in CMs 21, 56 ; however, this phenotype was associated with CM hypertrophy as well as AKT co-activation, which was absent in caBRAF ECTs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ERK may also respond to pressure and/or curvature, as reported for the lung epithelium Hirashima and Matsuda (2021) . In epithelial cells from the mammary gland, ERK activity has been found sensitive to the stiffness of the surrounding matrix Farahani et al (2021) . Whether any of this plays a role in the tracheal mesenchyme is not known.…”
Section: Control Of Cartilage Ring Formationmentioning
confidence: 99%